Forme e pratiche del pluralismo religioso nello Stato di Israele. L’eredità ottomana e la tutela dei rapporti familiari (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Israele, uno Stato ‘ebraico’ e multiculturale? - 2. Il sistema degli statuti personali e la tutela delle relazioni familiari - 3. Matrimoni, divorzi e Corti religiose - 4. Pluralismo, multiconfessionismo e dinamiche demografiche. Prime conclusioni e prospettive di ricerca.Forms and practices of the religious pluralism in the State of Israel. The Ottoman inheritance and the protection of family relationships.ABSTRACT: The essay aims to explore, also in a historical perspective, the general characteristics, peculiarities and limits of the differentiated protection of family relationships in force in the legal system of (State of Israel), still based on the millet system. It allows the application of the personal statutes of the various ethnic-religious communities (Jewish, Muslim, Druze, Christian) present on the territory, not only to regulate the legal institutions typical of family law - especially marriage and divorce -, but also for the resolution of disputes on the matter that are devolved to the jurisdiction of the religious Courts of several religions. In examining the effectiveness and functionality of this model of religious and cultural pluralism, the study highlights the delicate problems of relevance and coexistence of the different religious normative complexes in the Israeli state system.